STORE ATMOSPHERE DALAM MENCIPTAKAN EMOSI dan PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN (Survey pada Pengunjung Alfamart, Jalan Soekarno Hatta, Ruko Center Point, Kota Malang) - Zaini Kurniawan, Mochammad Lukman; Fauzi DH, Achmad; Kumadji, Srikandi (Profit: Jurnal Adminsitrasi Bisnis, 2015)
The purpose this study to determine and explain whether there influence between Store Atmosphere, Emotion and Purchase Decision. This is causality research. Methods data collection using a survey. The population were all those people who have made purchases transaction in Alfamart minimarket, in Center Point. Sampling method using Non-Probability Sampling with questionnaires and analyzed using Partial Least Square. Results of this study are: 1) Store Exterior is significant to Purchasing Decision Structure, 2) Store Exterior is not significant to Pleasure, 3) Store Exterior is significant to Arousal, 4) Store Exterior is significant to Dominance, 5) Store Interior is significant to Pleasure, 6) Store Interior is significant to Arousal, 7) Store Interior is significant to Dominance, 8) Store Layout is not significant to Pleasure, 9) Store Layout is significant to Arousal, 10) Store Layout is significant to Dominance, 11) Interior Display of Store is significant to Pleasure, 12) Interior Display of Store is not significant to Arousal, 13) Interior Display of Store is significant to Dominance, 14) Interior Display of Store is significant to Purchasing Decision Structure, 15) Pleasure is significant to Purchasing Decision Structure, 16) Arousal is significant to Purchasing Decision Structure, 17) Dominance is significant to Purchasing Decision Structure.Â